PENEGAKAN HUKUM TERHADAP PELAKU PERDAGANGAN SATWA DILINDUNGI DI WILAYAH HUKUM PENGADILAN NEGERI IDI - Muhammad Iqbal; M. Yamin Lubis; Nelvitia Purba (Jurnal Ilmiah METADATA, 2021)
The legal arrangements for the criminal act of trafficking in endangered species in the jurisdiction of the IDI District Court are specifically regulated in Law No.5 / 1990 on BKSDA and Qanun Number 11 of 2019 concerning Wildlife Management. In both regulations, there are several actions that are prohibited, including trading protected wild animals as regulated in Article 21 paragraph (2) of Law no. 5/1990 on BKSDA. Law enforcement against traffickers of endangered species in the jurisdiction of the IDI District Court is still not maximal. It is known from 11 cases of elephant deaths that occurred in 2018, only one case was successfully resolved by investigators, and examined and tried by the IDI District Court. Barriers encountered in law enforcement against perpetrators of endangered wildlife trade are influenced by the substance of the law, law enforcement, facilities and infrastructure, and community factors.